Characterization of AgCl crystal at low temperatures. (2022) - Pandey, Krishna Kumar
Abstract: In the present research work, Silver Chloride (AgCl) crystal has been characterized at the low temperature region i.e. below 100 K. It is very important to characterize it because of its various uses in electrochemistry, photochromic lenses etc. For this purpose, Acoustical methods such as the Ultrasonic waves have been used as a tool. The two parameters such as nearest-neighbour distance and hardness parameter have been used as two input parameters for the present research work. The second and third order elastic Moduli (SOEM and TOEM) have been calculated for AgCl. Then by using this data of SOEM and TOEM, the ultrasonic attenuation coefficient at low temperature region i.e. due to the cause of electron–phonon interaction is obtained.